2011
DOI: 10.1093/cercor/bhr225
|View full text |Cite
|
Sign up to set email alerts
|

A Human Mutation in Gabrg2 Associated with Generalized Epilepsy Alters the Membrane Dynamics of GABAA Receptors

Abstract: Neuronal activity modulates the membrane diffusion of postsynaptic γ-aminobutyric acid (GABA)(A) receptors (GABA(A)Rs), thereby regulating the efficacy of GABAergic synapses. The K289M mutation in GABA(A)Rs subunit γ2 has been associated with the generalized epilepsy with febrile seizures plus (GEFS+) syndrome. This mutation accelerates receptor deactivation and therefore reduces inhibitory synaptic transmission. Yet, it is not clear why this mutation specifically promotes febrile seizures. We show that upon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 60 publications
4
27
0
1
Order By: Relevance
“…Our data suggest that the ␥2(R43Q) mutant is a useful model for this purpose. Our findings also illustrate the fact that mutations offer insights not only into diseases but also receptor physiology (61,64,74,76). It would be also of interest to assess whether the different allosteric drugs acting on GABA A Rs have an influence on receptor trafficking.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Our data suggest that the ␥2(R43Q) mutant is a useful model for this purpose. Our findings also illustrate the fact that mutations offer insights not only into diseases but also receptor physiology (61,64,74,76). It would be also of interest to assess whether the different allosteric drugs acting on GABA A Rs have an influence on receptor trafficking.…”
Section: Resultsmentioning
confidence: 61%
“…For example, status epilepticus leads to enhanced GABA A R endocytosis (28 -30). The K289M substitution in the ␥2 subunit known to be responsible for generalized epilepsy with febrile seizures plus alters the membrane diffusion of GABA A Rs (61). It must be also noted that a shortened lifetime caused by the epilepsy mutation A322D on ␣1-containing GABA A Rs has been proposed (74) (but also see Ref.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Altogether, this supports a model whereby BZ-induced conformational changes directly regulate receptor diffusion by changing the interaction of the receptor with scaffolding proteins. Along the same line, recent studies proposed an allostery-dependent mechanism affecting GABA A R diffusion (Bouthour et al, 2012;Levi et al, in press).…”
Section: Discussionmentioning
confidence: 88%
“…We previously showed that a human mutation in the GABAAR g2 subunit (Baulac et al, 2001) that promotes the closed state of the GABAA receptor (Bianchi et al, 2002;Eugene et al, 2007) increases its membrane diffusion and reduces its clustering at synapses (Bouthour et al, 2011). We asked whether pharmacological manipulation of the allosteric state of the receptor could similarly impact its membrane dynamics and synaptic mobilization.…”
Section: Dmcm Increases Membrane Diffusion and Reduces Synaptic Stabimentioning
confidence: 99%
“…We recently reported that a point mutation in GABAAR g2 subunit associated with generalized epilepsy (Baulac et al, 2001) affects both the gating kinetics (Bianchi et al, 2002;Eugene et al, 2007) and the membrane dynamics and synaptic aggregation of the receptor (Bouthour et al, 2011). Since this mutation is located in the second extracellular domain of g2 (Baulac et al, 2001), it is unlikely to directly affect GABAAR interaction with submembrane gephyrin scaffold.…”
Section: Introductionmentioning
confidence: 99%